The international experience of bacterial screen testing of platelet components with automated microbial detection systems: An update. Issue 5 (17th February 2022) - Kamel, Hany; Ramirez‐Arcos, Sandra; McDonald, Carl; ,
Abstract: In 2014, the bacterial subgroup of the Transfusion‐Transmitted Infectious Diseases working party of ISBT published a review on the International Experience of Bacterial Screen Testing of Platelet Components (PCs) with an Automated Microbial Detection System. The purpose of this review, which is focused on publications on or after 2014, is to summarize recent experiences related to bacterial contamination of PCs and the use of an automated culture method to safeguard the blood supply. We first reviewed septic transfusion reactions after PC transfusion as reported in national haemovigilance systems along with a few reports from various countries on bacterial contamination of blood products. Next, we reviewed PC automated culture protocols employed by national blood services in the United Kingdom, Australia, Canada and large blood collection organization and hospital transfusion services in the United States. Then, we acknowledged the limitations of currently available culture methodologies in abating the risks of transfusion‐transmitted bacterial infection, through a review of case reports. This review was neither meant to be critical of the literature reviewed nor meant to identify or recommend a best practice. We concluded that significant risk reduction can be achieved by one or a combination of more than one strategy. No one approach is feasible for all institutions worldwide. In selecting strategies, institutions should consider the possible impact on platelet components availability and entertain a risk‐based decision‐making approach that accounts for operational, logistical and financial factors.